Prognosis and cardiotoxicity associated to adjuvant trastuzumab for breast cancer: real world study in a public health system - Ana Elisa Ribeiro da Silva Cabello; César Cabello; Susana Oliveira Botelho Ramalho; Otávio Rizzi Coelho; Otávio Rizzi Coelho-Filho; Helymar da Costa Machado; Délio Marques Conde; Luiz Carlos Zeferino (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: To analyze the prognosis of patients with breast cancer who developed trastuzumab-induced cardiotoxicity and to analyze factors associated with and resulting from cardiotoxicity. Methods: This was a retrospective cohort study that included 255 HER2-positive breast cancer patients who received adjuvant trastuzumab therapy. The inclusion criteria were a diagnosis of HER2-positive breast cancer and adjuvant trastuzumab therapy; disease stage I-III; <70 years; and a baseline echocardiogram showing a left ventricular ejection fraction (LVEF) ≥ 55%. The Kaplan-Meier method, the log-rank test, and the Cox proportional hazards model were used. Results: In all, 15.3% (39/255) of patients presented with cardiotoxicity. Treatment was suspended in 92.3% (36/39) of patients who presented with cardiotoxicity during trastuzumab treatment. The treatment was suspended in 46 of 255 patients and it was permanently interrupted in 84.8% (33/46) of these patients, with 84.8% (28/33) due to cardiotoxicity. Cardiotoxicity was not associated with disease-free survival (DFS) (hazard ratio (HR) = 1.48; 95% confidence interval (CI = 0.79-2.78) or overall survival (OS) (HR = 1.68; 95%CI= 0.83-3.41). Patients with clinical stage III and whom trastuzumab therapy was suspended (all causes) had worse DFS; (HR = 3.19; 95% CI=1.77-5.74) and (HR = 1.83; 95% CI=1.01-3.32) respectively. Those with clinical stage III and whom trastuzumab therapy was permanently interrupted had worse OS; (HR = 3.80; 95% CI =1.82-7.94), and (HR = 2,26; 95% CI =1.09-4.68 respectively. Conclusion: Cardiotoxicity was not associated with DFS or OS. Clinical stage III, Suspension and permanent interruption of treatment regardless of the cause were associated with worse DFS and OS in breast cancer patients.